METHODOLOGICAL FOUNDATIONS OF THE DEVELOPMENT OF HUMAN PHYSICAL QUALITIES - Yormatov Gulomjon; Maksudov Ravshan Alievich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article, the movement skills being taught are close to each other in terms of the amplitude and nature of the exercises, and information on the use of movement games that are close to or suitable for the movement technique being taught in this regard.